Improving Moringa growth by using autochthonous and allochthonous arbuscular mycorrhizal fungi in Lake Victoria basin - Knopfl, E; Blaschke, H; Munch, J.C (West African journal of applied ecology, 2013)
Biological methods such as mycorrhiza biotechnology used for raising and sustaining soil fertility in agricultural ecosystems close to freshwater biomes are gaining attention. However, ubiquitous ecological conditions may subject mycorrhizal management to choices that depend on inoculum sources (autochthonous or cultured). Effects of AMF on growth of M. stenopetala and M. oleifera were evaluated using three native soil types, representative of Lake Victoria basin and a standard substrate. Autochthonous AMF was harnessed from the native soils while allochthonous AMF cocktail was acquired from culture banks of Glomus hoi, G. mosseae and G. intraradices, using Plantago major as plant indicator and trap-culture. The soils were blocked according to tillage intensities. P. major supplied Moringa with AMF inoculum. To facilitate mycorrhization, nitrogen fixing bacteria (NFB) in chickpea rhizobia inoculum was integrated. The hyphopodium assays revealed > 90% arbuscle occupancy in root cortex of plants established in paddy LT soils. AMF inoculation improved growth and biomass of both Moringa species. Autochthonous AMF inoculum had relatively higher biomass turnover compared to cultured AMF. The presence of dark septate endophytes (DSE) in plant biodiversity gave a new insight into target plant performance at plant competition for nutrients. Results reveal that inoculum AMF and NFB are potential candidates in optimizing plant production technology applicable in eco-sensitive-oriented low in-put agriculture.